Preparation method and application of manganese-doped acidic Beta zeolite molecular sieve containing mesoporous structure
The manganese-doped acidic Beta zeolite molecular sieve catalyst M-Mn-Beta synthesized by in-situ doping hydrothermal method solves the problems of high cost and difficult recovery in the prior art, and realizes the efficient catalytic decarboxylation coupling reaction between cinnamic acid and sodium benzenesulfinate. The yield is high and the catalyst is stable, and it is suitable for organic synthesis in multiple fields.
Patent Information
- Application Number
- CN202311372178.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-23
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-10-23
AI Technical Summary
The homogeneous catalyst used in the prior art to catalyze the synthesis of styrene sulfone with cinnamic acid and sodium benzenesulfinate has problems such as high cost, difficulty in recycling, large energy consumption, and heavy metal pollution, which is difficult to meet the requirements of sustainable chemistry and green chemistry.
The in-situ doping hydrothermal method was used to synthesize the acidic Beta zeolite molecular sieve catalyst M-Mn-Beta containing mesoporous structures, which was used to catalyze the decarboxylation reaction of cinnamic acid and sodium benzenesulfinate.
The efficient catalytic reaction of cinnamic acid and sodium benzenesulfinate decarboxylation coupling reaction is achieved, and the yield of styrene sulfone is as high as 95%. The catalyst has good stability and recycling properties, and is suitable for organic synthesis, medicinal chemistry and materials science.
Smart Images

Figure CN117430125B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of organic catalytic synthesis, and specifically relates to a preparation method and application of a manganese-doped acidic Beta zeolite molecular sieve containing a mesoporous structure. Background Art
[0002] Vinyl sulfone compounds are an important class of organic molecules, widely used in the fields of medicinal chemistry and organic synthetic chemistry. For example, vinyl sulfone compounds are important structural fragments in many drugs, such as cysteine protease inhibitors, membrane protein transpeptidase inhibitors, HIV-1 integrase inhibitors, etc. In addition, in organic synthesis, they are also widely used as Michael receptors, etc.
[0003] At present, there are many methods for synthesizing vinyl sulfone compounds, such as oxidation of vinyl sulfide, reduction of acetylene sulfone, condensation of aromatic aldehydes and sulfonylacetic acid, β-elimination of selenosulfone or halogenated sulfone, coupling of alkenylboronic acid and sodium benzenesulfinate, decarboxylation sulfonylation of cinnamic acid and its derivatives with sodium sulfinate, ring-opening reaction of terminal epoxide with sodium sulfinate, etc. Among them, the decarboxylation sulfonylation reaction of cinnamic acid and sodium benzenesulfinate to synthesize vinyl sulfone compounds is considered to be the most efficient and very promising synthesis method. Since the reactant cinnamic acid can be directly prepared from aromatic aldehydes through the Perkin reaction, it is an easily available, inexpensive, and structurally stable molecule. The byproduct of the decarboxylation sulfonylation reaction is non-toxic CO2. In 2014, Tan Ze et al. used cinnamic acid and sodium benzenesulfinate as raw materials, Pd(OAc)2 and 1,4-bis(diphenylphosphino)butane (dppb) as catalysts, Ag2CO3 as additives, and DMF as solvent. The reaction was carried out at 75°C for 6 hours to obtain the product vinyl sulfone with a yield of 45-94% (R. Guo, Q. Gui, D. Wang, Z. Tan. Catal. Lett., 2014, 144, 1377-1383). Xiang Jiannan et al. from Hunan University used derivatives of cinnamic acid and sodium benzenesulfinate as raw materials, Mn(OAc)2 as catalyst, DMSO as solvent, and reacted at 110°C for 12 hours. The yield of vinyl sulfone was 57-86% (N.Xue, R.Guo, X.Tu, W.Luo, W.Deng, J.Xiang.Synlett, 2016, 27, 2695-2698). In addition, diacetoxyiodobenzene (PhI(OAc)2), I2 / TBHP, K2CO3, etc. can all catalyze decarboxylation and sulfonylation to synthesize vinyl sulfone (P.Katrun, S.Hlekhlai, J.Meesin, M.Pohmakotr, V.Reutrakul, T.Jaipetch, D.Soorukram, C.Kuhakarn, Org.Biomol.Chem.,2015,13,4785-4794; R.Singh, B.Allam, N.Singh, K.Kumari, S.Singh, K.Singh, Org.Lett.,2015,17,2656-2659; Y.Xu, X.Tang, W.Hu, W.Wu, H.Jiang,Green Chem.,2014,16,3720-3723).
[0004] However, the reported works all use homogeneous catalysts, which have the problems of high cost, difficulty in recycling, high energy consumption, heavy metal pollution, etc., and do not meet the requirements of sustainable chemistry and green chemistry. Guo Cancheng et al. used cinnamic acid and sodium benzenesulfinate as raw materials, CuO (20mol%) as catalyst, KI as additive, DMSO as solvent, reacted at 100°C for 24 hours, and obtained styryl sulfone by decarboxylation sulfonylation reaction, with a yield of 74%, but there are problems such as long reaction time, large amount of catalyst used, and the product yield cannot be further improved (Q. Jiang, X. Bin, J. Jiang, A. Zhao, Y. Zhao, Y. Li, N. He, C. Guo. J. Org. Chem., 2014, 79, 7372-7379). Therefore, it is of great significance to develop a highly active, low-cost, green and recyclable heterogeneous catalyst for efficient catalysis of cinnamic acid and sodium benzenesulfinate to synthesize styryl sulfone.
[0005] Beta zeolite molecular sieve has a large specific surface area, rich and ordered pore structure, high thermal stability and acid sites, which are conducive to the adsorption, catalysis and desorption of reactants, making it widely used in various catalytic fields such as petrochemicals, fine chemicals and environmental protection as a kind of green and environmentally friendly heterogeneous catalyst. The active metal Mn-doped Beta molecular sieve catalyst not only has the advantages of Beta molecular sieve, but also the Mn ions introduced into the molecular sieve framework increase the catalytic active sites. Xia Qinghua et al. prepared Mn-Beta molecular sieve by ion exchange method and used it to catalyze the epoxidation reaction of olefins with H2O2. The catalyst showed good catalytic performance for olefins with smaller size or electron-rich terminal olefins, and the catalyst still maintained high catalytic activity after repeated recycling (B.Qi, X.Lu, D.Zhou, Q.Xia, Z.Tang, S.Fang, T.Pang, Y.Dong, J.Mol.Catal.A:Chem., 2010, 322, 73-79). Zhang Guangxu et al. prepared Mn / Beta molecular sieve by impregnation method, and selectively catalyzed NO reduction to N2. At 240°C, the NO conversion rate was as high as 97.5%, which may be due to the high surface Mn content and surface active oxygen groups and the appropriate content of weak acid sites, which are conducive to the reaction (W.Xu, G.Zhang, H.Chen, G.Zhang, Y.Han, Y.Chang, P.Gong, Chinese J.Catal., 2018, 39, 118-127). However, so far, there is no relevant literature report on the application of Mn-doped acidic Beta zeolite molecular sieve containing mesoporous structure to catalyze the decarboxylation coupling reaction of cinnamic acid and sodium benzenesulfinate to synthesize styryl sulfone compounds.
[0006] Therefore, it is of great scientific significance and application value to research and develop manganese-containing mesoporous acidic Beta molecular sieves with high activity, good stability and recyclability, and to use them to efficiently catalyze the decarboxylation sulfonylation reaction of cinnamic acid and sodium benzenesulfinate to synthesize styrene-based compounds. Summary of the invention
[0007] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0008] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0009] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a manganese-doped acidic Beta zeolite molecular sieve containing a mesoporous structure, characterized in that: the structure of the molecular sieve is Mn-nSi-Al-Beta, wherein n represents the molar ratio of Si / Al, n=20-60;
[0010] The acidic Beta zeolite molecular sieve has a characteristic X-ray powder diffraction pattern as shown below:
[0011]
[0012] The X-ray powder diffraction pattern is based on a relative intensity scale, wherein the strongest line in the X-ray powder diffraction pattern is assigned a value of 100, and the corresponding relative intensities are: w represents weak, i.e. ≤20; m represents medium, i.e. >20 to ≤40; s represents strong, i.e. >40 to ≤60; and vs represents very strong, i.e. >60.
[0013] As a preferred embodiment of the acidic Beta zeolite molecular sieve of the present invention, the specific surface area of the acidic Beta zeolite molecular sieve is 435 to 693 m 2 / g, the silicon-aluminum ratio is 20:1-60:1, and the crystallinity is 85-100%.
[0014] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing an acidic Beta zeolite molecular sieve, comprising:
[0015] Mix silicic acid, manganese salt and deionized water evenly, add concentrated hydrochloric acid dropwise to adjust the pH to 1.0, then add quaternary ammonium salt and sodium aluminate, stir evenly and adjust the pH of the solution to 12.5 with sodium hydroxide;
[0016] The mixed solution is transferred to a hydrothermal autoclave with a polytetrafluoroethylene liner and crystallized at a constant temperature for a period of time;
[0017] The product was washed with deionized water and anhydrous ethanol, dried, and calcined at 550° C. for 5 hours to obtain a manganese-doped acidic Beta molecular sieve catalyst M-Mn-Beta containing a mesoporous structure.
[0018] As a preferred embodiment of the preparation method of the present invention, the molar ratio of the silicic acid to the sodium aluminate is 20:1 to 60:1.
[0019] As a preferred embodiment of the preparation method of the present invention, the quaternary ammonium salt is one or more of tetraethylammonium bromide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, and hexadecyltrimethylammonium bromide, and 1.2 to 3 g of the quaternary ammonium salt is corresponding to 1 g of silicic acid; the manganese salt is one or more of manganese nitrate, manganese acetate, manganese sulfate, and manganese chloride, and 0.03 to 0.1 g of the manganese salt is corresponding to 1 g of silicic acid.
[0020] As a preferred embodiment of the preparation method of the present invention, the crystallization is carried out at a constant temperature for a period of time, wherein the crystallization temperature is 100-200° C. and the crystallization time is 5-15 days.
[0021] Another object of the present invention is to overcome the deficiencies in the prior art and provide an application of an acidic Beta zeolite molecular sieve, characterized in that the acidic Beta zeolite molecular sieve is used to catalyze the decarboxylation sulfonylation reaction of cinnamic acid and sodium benzenesulfinate to prepare a vinyl sulfone compound, wherein the preparation method is to mix cinnamic acid, sodium benzenesulfinate, an acidic Beta molecular sieve catalyst M-Mn-Beta, an additive and a solvent, and react at 50 to 150° C. for 1 to 24 hours to obtain a vinyl sulfone silicon compound.
[0022] As a preferred embodiment of the application of the present invention, the cinnamic acid is cinnamic acid and its derivatives, at least one of 2-methylcinnamic acid, 3-methylcinnamic acid, 2-ethoxycinnamic acid, 4-methoxycinnamic acid, 3-fluorocinnamic acid, 4-fluorocinnamic acid, 2,4-difluorocinnamic acid, 2-chlorocinnamic acid, 3-chlorocinnamic acid, 4-chlorocinnamic acid, and 3-bromocinnamic acid; the sodium benzenesulfinate is sodium benzenesulfinate and its derivatives, at least one of 4-methylbenzenesulfinate, 4-fluorobenzenesulfinate, and 4-chlorobenzenesulfinate; the molar ratio of cinnamic acid to sodium benzenesulfinate is 1:1 to 1:5; and the added amount of the acidic Beta molecular sieve catalyst M-Mn-Beta is 0.1 to 5 mol% of the amount of cinnamic acid.
[0023] As a preferred embodiment of the application of the present invention, the additive is one of KI, NaI, NH4I, I2, K2CO3, KCl, and KBr, and every 0.1 mmol of cinnamic acid corresponds to 0.1 to 0.5 mmol of the additive; the solvent is one or more of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, dichloroethane, N-methylpyrrolidone, water, and ethanol, and every 0.1 mmol of cinnamic acid corresponds to 0.2 to 2 ml of the solvent.
[0024] As a preferred embodiment of the application of the present invention, the vinyl sulfone silicon compound can be applied to the fields of catalytic organic synthesis chemistry, medicinal chemistry, and material science.
[0025] Beneficial effects of the present invention:
[0026] (1) The M-Mn-Beta molecular sieve catalyst synthesized by the in-situ doping hydrothermal method of the present invention has the advantages of easy separation, high activity, good stability, long service life and long storage time. Compared with the ion exchange method and the impregnation method, the M-Mn-Beta molecular sieve synthesized by the in-situ doping hydrothermal method not only prevents the aggregation of Mn particles and ensures that the active Mn species are stably and evenly dispersed on the Beta molecular sieve containing the mesoporous structure, but also the synthesized molecular sieve catalyst has good crystallinity and reduces the loss of active metal Mn. The synthesis method of the present invention is easy to operate, has simple equipment requirements and good reproducibility.
[0027] (2) The M-Mn-Beta molecular sieve catalyst synthesized by the present invention contains Lewis acidic active sites that can promote the conversion of sodium benzenesulfinate into the corresponding benzenesulfinic acid free radicals. The Mn species can coordinate with the carboxyl oxygen atoms in the cinnamic acid molecules, significantly improving the activity of the reaction substrate. At the same time, the molecular sieve has a high specific surface area and contains a mesoporous structure that allows the reactant molecules to easily contact the active sites, which is beneficial to the diffusion of reactant and product molecules. The formed benzenesulfinic acid free radical molecules further undergo a decarboxylation coupling reaction with the cinnamic acid active molecules, removing a molecule of carbon dioxide to generate the product (E)-(2-(phenylsulfonyl)vinyl)benzene. This synergistic catalytic effect significantly improves the catalytic activity of the M-Mn-Beta molecular sieve.
[0028] (3) Experiments show that the mesoporous M-Mn-Beta molecular sieve prepared by the present invention has higher catalytic decarboxylation coupling reaction performance, and the yield of catalyzing the decarboxylation sulfonylation of cinnamic acid and sodium benzenesulfinate to generate styryl sulfone compounds is as high as 95%. It can be applied in the fields of organic synthesis, organometallic chemistry, medicinal chemistry and material science, and has certain industrial utilization value. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0030] Figure 1 This is a scanning electron microscope image of the M-Mn-Beta molecular sieve catalyst prepared in Example 1 of the present invention;
[0031] Figure 2 The X-ray powder diffraction pattern of the M-Mn-Beta molecular sieve catalyst and the standard Beta in Example 1 of the present invention;
[0032] Figure 3 It is a N2 adsorption-desorption curve diagram of the M-Mn-Beta molecular sieve catalyst in Example 1 of the present invention;
[0033] Figure 4 NH3-TPD curve of the M-Mn-Beta molecular sieve catalyst in Example 1 of the present invention;
[0034] Figure 5 The product (E)-(2-(phenylsulfonyl)vinyl)benzene obtained by the decarboxylation coupling reaction of cinnamic acid and sodium benzenesulfinate catalyzed by the M-Mn-Beta molecular sieve prepared in Example 1 of the present invention is 1 H NMR spectrum;
[0035] Figure 6 The product (E)-(2-(phenylsulfonyl)vinyl)benzene obtained by the decarboxylation coupling reaction of cinnamic acid and sodium benzenesulfinate catalyzed by the M-Mn-Beta molecular sieve prepared in Example 1 of the present invention is 13 C NMR spectrum;
[0036] Figure 7 This is a diagram showing the catalytic effect of the M-Mn-Beta molecular sieve catalyst prepared in Example 1 of the present invention being recycled six times. DETAILED DESCRIPTION
[0037] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0038] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0039] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0040] The specifications of the chemical reagents used in the embodiments of the present invention are shown in Table 1.
[0041] Table 1 Specifications and other information of chemical reagents used in the experiment
[0042]
[0043]
[0044] Example 1
[0045] The preparation method of M-Mn-Beta molecular sieve material comprises the following steps:
[0046] Weigh 5.3g of silicic acid and 0.3g of manganese chloride tetrahydrate, dissolve in deionized water and mix well, add concentrated hydrochloric acid drop by drop to adjust the pH of the solution to 1.0, then add 13.7g of 25% tetraethylammonium hydroxide aqueous solution and 0.4g of sodium aluminate, stir well and adjust the pH of the solution to 12.5 with sodium hydroxide;
[0047] The mixed solution was transferred to a 50 ml polytetrafluoroethylene high pressure hydrothermal autoclave and crystallized at 140 °C for 14 days;
[0048] The product was washed with deionized water and anhydrous ethanol until neutral, dried, transferred to a muffle furnace and calcined at 550° C. for 5 hours to obtain the product M-Mn-Beta molecular sieve.
[0049] The product mass was measured to be 2.5 g, the metal content was 1.8 wt%, and the specific surface area was 693 m 2 / g, and the crystallinity is 100%. The information of the equipment models used in the experiment of the present invention is shown in Table 2.
[0050] Table 2. Information on the equipment used in the experiment.
[0051]
[0052] The M-Mn-Beta molecular sieve material prepared in Example 1 was characterized.
[0053] Thermo Scientific Apreo 2C field emission scanning electron microscope (SEM) was used to analyze the morphology and structure of M-Mn-Beta. Figure 1As shown, the scale sizes are 2μm, 1μm, and 200nm respectively. The results show that the morphology of the M-Mn-Beta molecular sieve is relatively regular and uniform, mainly in the form of egg-shaped aggregates with a diameter of 600nm, and each aggregate is assembled from multiple primary BEA crystals of about 30nm. The mutual accumulation of these aggregates will produce many accumulation holes, which is conducive to the dispersion of metal species and the contact of reactant molecules with active sites.
[0054] The crystal structure and phase of the M-Mn-Beta molecular sieve material were analyzed using a Rigaku D / MAX-2500PC X-ray powder diffractometer (PXRD, Cu Kα radiation, λ=0.154 nm, scanning range 2θ 5° to 50°, scanning speed 2° / min). The analysis results are shown in Figure 2 As shown in Table 3, the results show that the crystal phase structure of M-Mn-Beta molecular sieve is completely matched with that of Beta molecular sieve, and both have a typical BEA structure, indicating the successful preparation of M-Mn-Beta molecular sieve. In addition, the characteristic diffraction peak of Mn species cannot be detected in the figure, which indicates that the small particles of Mn species are highly uniformly dispersed on the Beta molecular sieve. From the peak intensity point of view, the peak intensity of M-Mn-Beta is strong and the peak shape is sharp, indicating that the crystallinity of M-Mn-Beta molecular sieve material is good, which provides a guarantee for its use as a catalyst for the decarboxylation coupling reaction of cinnamic acid.
[0055] Table 3
[0056]
[0057] Micrometrics ASAP2460 specific surface area and porosity analyzer was used to measure the specific surface area, N2 adsorption-desorption curve and pore size distribution of M-Mn-Beta molecular sieve material. The specific surface area was determined by the BET method, and the pore size distribution was determined by the BJH method. Before the measurement, the sample was dried at 120°C for 2 hours and then placed in a vacuum environment at 150°C for 12 hours. The measurement results are as follows: Figure 3 As shown in the figure, the N2 adsorption-desorption isotherm has a hysteresis loop at the relative pressure P / P0=0.5-0.99, which is due to the capillary condensation of N2 in the pores of the molecular sieve, further indicating that M-Mn-Beta contains a mesoporous structure. From the pore size distribution curve, it can be seen that the pore size of M-Mn-Beta is mainly distributed at 3.7nm and 4.3nm, and the pore size distribution is uniform.
[0058] The acidity of the catalyst was measured using ammonia temperature programmed desorption (NH3-TPD) on a Micrometrics AUTO Chem II 2920 instrument. Figure 4As shown, the desorption temperature of NH3 is 123.5℃, which belongs to the weak acid center range, and further indicates that the M-Mn-Beta molecular sieve has a relatively moderate weak acid strength.
[0059] Comparative Example 1
[0060] The ion exchange method for synthesizing the M-Mn-Beta molecular sieve catalyst comprises the following steps:
[0061] (1) Synthesize M-Beta molecular sieve by hydrothermal method:
[0062] Weigh 5.3g of silicic acid and dissolve it in deionized water and mix well. Add concentrated hydrochloric acid to adjust the pH to 1.0. Then add 13.7g of 25% tetraethylammonium hydroxide aqueous solution and 0.4g of sodium aluminate. Stir well and adjust the pH of the solution to 12.5 with sodium hydroxide.
[0063] The mixed solution was transferred to a 50 ml polytetrafluoroethylene high pressure hydrothermal autoclave and crystallized at 140 °C for 14 days;
[0064] The product was washed with deionized water and anhydrous ethanol, dried, transferred to a muffle furnace and calcined at 550° C. for 5 hours to obtain the product M-Beta molecular sieve.
[0065] (2) Preparation of M-Mn-Beta molecular sieve by ion exchange method:
[0066] Weigh 0.3 g of manganese chloride tetrahydrate, add 10 ml of deionized water to dissolve it, stir evenly, add the M-Beta molecular sieve prepared above, stir, perform ion exchange at room temperature, dry at 100° C. overnight, press into tablets and sieve to obtain M-Mn-Beta molecular sieve.
[0067] The product mass was measured to be 1.7 g, the metal content was 1.5 wt%, and the specific surface area was 616 m 2 / g, and the crystallinity is 80%.
[0068] Comparative Example 2
[0069] The preparation of M-Mn-Beta by equal volume impregnation method includes the following steps:
[0070] First, the water absorption rate of the Beta molecular sieve carrier is measured, and the catalyst is impregnated in equal volumes according to the water absorption rate. Weigh 0.3g of manganese chloride tetrahydrate and dissolve it in deionized water. Add 1g of M-Beta molecular sieve carrier (silicon-aluminum ratio 40, crystallinity 100%) and stir it thoroughly, and mix it evenly with ultrasound. After aging at room temperature for 5 hours, dry it at 80℃, and calcine it at 550℃ in a muffle furnace for 5 hours to obtain M-Mn-Beta molecular sieve.
[0071] The product mass was measured to be 1.9 g, the metal content was 1.7 wt%, and the specific surface area was 658 m 2 / g, and the crystallinity is 85%.
[0072] It can be seen from Example 1 and Comparative Examples 1 and 2 that the in-situ doping synthesis method has the advantages of more convenient operation, high catalyst yield, high crystallinity, etc. compared with the ion exchange method and the impregnation method. In addition, the interaction between the Mn species in the M-Mn-Beta catalyst synthesized by in-situ doping hydrothermal synthesis and the M-Beta molecular sieve is stronger, so that Mn is highly dispersed on the molecular sieve, and thus has a higher catalytic activity. The following examples screen the raw materials or ratios and other condition parameters for synthesizing M-Mn-Beta by in-situ doping.
[0073] Example 2
[0074] Weigh 5.3g of silicic acid and 0.2g of manganese chloride tetrahydrate, dissolve in deionized water and mix well, add concentrated hydrochloric acid dropwise to adjust the pH of the solution to 1.0, then add 13.7g of 25% tetraethylammonium hydroxide aqueous solution and 0.4g of sodium aluminate, stir well, and then adjust the pH of the solution to 12.5 with sodium hydroxide;
[0075] The mixed solution was transferred to a 50 ml polytetrafluoroethylene high pressure hydrothermal autoclave and crystallized at 140 °C for 14 days;
[0076] The product was washed with deionized water and anhydrous ethanol until neutral, dried, transferred to a muffle furnace and calcined at 550° C. for 5 hours to obtain the product M-Mn-Beta molecular sieve.
[0077] The product mass was measured to be 2.3 g, the metal content was 1.3 wt%, and the specific surface area was 671 m 2 / g, and the crystallinity is 98%.
[0078] Example 3
[0079] Weigh 5.3g of silicic acid and 0.3g of manganese nitrate tetrahydrate, dissolve in deionized water and mix well, add concentrated hydrochloric acid drop by drop to adjust the pH of the solution to 1.0, then add 13.7g of tetraethylammonium bromide and 0.4g of sodium aluminate, stir well, and adjust the pH of the solution to 12.5 with sodium hydroxide;
[0080] The mixed solution was transferred to a 50 ml polytetrafluoroethylene high pressure hydrothermal autoclave and crystallized at 140 °C for 14 days;
[0081] The product was washed with deionized water and anhydrous ethanol until neutral, dried, transferred to a muffle furnace and calcined at 550° C. for 5 hours to obtain the product M-Mn-Beta molecular sieve.
[0082] The product mass was measured to be 2.1 g, the metal content was 1.4 wt%, and the specific surface area was 593 m 2 / g, and the crystallinity is 83%.
[0083] Example 4
[0084] Weigh 5.3g of silicic acid and 0.5g of manganese acetate dihydrate, dissolve in deionized water and mix well, add concentrated hydrochloric acid drop by drop to adjust the pH of the solution to 1.0, then add 13.7g of tetrapropylammonium hydroxide and 0.4g of sodium aluminate, stir well, and then adjust the pH of the solution to 12.5 with sodium hydroxide;
[0085] The mixed solution was transferred to a 50 ml polytetrafluoroethylene high pressure hydrothermal autoclave and crystallized at 140 °C for 14 days;
[0086] The product was washed with deionized water and anhydrous ethanol until neutral, dried, transferred to a muffle furnace and calcined at 550° C. for 5 hours to obtain the product M-Mn-Beta molecular sieve.
[0087] The product mass was measured to be 2.6 g, the metal content was 2.3 wt%, and the specific surface area was 622 m 2 / g, and the crystallinity is 87%.
[0088] Example 5
[0089] Weigh 5.3 g of silicic acid and 0.3 g of manganese sulfate tetrahydrate, dissolve in deionized water and mix well, add concentrated hydrochloric acid dropwise to adjust the pH of the solution to 1.0, then add 13.7 g of hexadecyltrimethylammonium bromide and 0.4 g of sodium aluminate, stir well, and then adjust the pH of the solution to 12.5 with sodium hydroxide;
[0090] The mixed solution was transferred to a 50 ml polytetrafluoroethylene high pressure hydrothermal autoclave and crystallized at 140 °C for 14 days;
[0091] The product was washed with deionized water and anhydrous ethanol until neutral, dried, transferred to a muffle furnace and calcined at 550° C. for 5 hours to obtain the product M-Mn-Beta molecular sieve.
[0092] The product mass was measured to be 2.2 g, the metal content was 1.5 wt%, and the specific surface area was 677 m 2 / g, and the crystallinity is 98%.
[0093] Example 6
[0094] Weigh 5.3g of silicic acid and 0.5g of manganese chloride tetrahydrate, dissolve in deionized water and mix well, add concentrated hydrochloric acid dropwise to adjust the pH of the solution to 1.0, then add 6.8g of 25% tetraethylammonium hydroxide aqueous solution and 0.4g of sodium aluminate, stir well, and adjust the pH of the solution to 12.5 with sodium hydroxide;
[0095] The mixed solution was transferred to a 50 ml polytetrafluoroethylene high pressure hydrothermal autoclave and crystallized at 140 °C for 14 days;
[0096] The product was washed with deionized water and anhydrous ethanol until neutral, dried, transferred to a muffle furnace and calcined at 550° C. for 5 hours to obtain the product M-Mn-Beta molecular sieve.
[0097] The product mass was measured to be 2.6 g, the metal content was 2.2 wt%, and the specific surface area was 532 m 2 / g, and the crystallinity is 91%.
[0098] Example 7
[0099] Weigh 5.3g of silicic acid and 0.3g of manganese chloride tetrahydrate, dissolve in deionized water and mix well, add concentrated hydrochloric acid dropwise to adjust the pH of the solution to 1.0, then add 9.8g of 25% tetraethylammonium hydroxide aqueous solution and 0.8g of sodium aluminate, stir well, and adjust the pH of the solution to 12.5 with sodium hydroxide;
[0100] The mixed solution was transferred to a 50 ml polytetrafluoroethylene high pressure hydrothermal autoclave and crystallized at 140 °C for 14 days;
[0101] The product was washed with deionized water and anhydrous ethanol until neutral, dried, transferred to a muffle furnace and calcined at 550° C. for 5 hours to obtain the product M-Mn-Beta molecular sieve.
[0102] The product mass was measured to be 2.1 g, the metal content was 1.6 wt%, and the specific surface area was 525 m 2 / g, and the crystallinity is 88%.
[0103] Example 8
[0104] Weigh 5.3g of silicic acid and 0.3g of manganese chloride tetrahydrate, dissolve in deionized water and mix well, add concentrated hydrochloric acid dropwise to adjust the pH of the solution to 1.0, then add 13.7g of 25% tetraethylammonium hydroxide aqueous solution and 0.26g of sodium aluminate, stir well, and then adjust the pH of the solution to 12.5 with sodium hydroxide;
[0105] The mixed solution was transferred to a 50 ml polytetrafluoroethylene high pressure hydrothermal autoclave and crystallized at 100 °C for 15 days;
[0106] The product was washed with deionized water and anhydrous ethanol until neutral, dried, transferred to a muffle furnace and calcined at 550° C. for 5 hours to obtain the product M-Mn-Beta molecular sieve.
[0107] The product mass was measured to be 1.8 g, the metal content was 1.1 wt%, and the specific surface area was 588 m 2 / g, and the crystallinity is 93%.
[0108] Example 9
[0109] Weigh 5.3g of silicic acid and 0.3g of manganese chloride tetrahydrate, dissolve in deionized water and mix well, add concentrated hydrochloric acid drop by drop to adjust the pH of the solution to 1.0, then add 13.7g of 25% tetraethylammonium hydroxide aqueous solution and 0.4g of sodium aluminate, stir well and adjust the pH of the solution to 12.5 with sodium hydroxide;
[0110] The mixed solution was transferred to a 50 ml polytetrafluoroethylene high pressure hydrothermal autoclave and crystallized at 150 °C for 7 days;
[0111] The product was washed with deionized water and anhydrous ethanol until neutral, dried, transferred to a muffle furnace and calcined at 550° C. for 5 hours to obtain the product M-Mn-Beta molecular sieve.
[0112] The product mass was measured to be 2.1 g, the metal content was 1.5 wt%, and the specific surface area was 615 m 2 / g, and the crystallinity is 96%.
[0113] Example 10
[0114] Weigh 5.3g of silicic acid and 0.3g of manganese chloride tetrahydrate, dissolve in deionized water and mix well, add concentrated hydrochloric acid drop by drop to adjust the pH of the solution to 1.0, then add 13.7g of 25% tetraethylammonium hydroxide aqueous solution and 0.4g of sodium aluminate, stir well and adjust the pH of the solution to 12.5 with sodium hydroxide;
[0115] The mixed solution was transferred to a 50 ml polytetrafluoroethylene high pressure hydrothermal autoclave and crystallized at 200 °C for 5 days;
[0116] The product was washed with deionized water and anhydrous ethanol until neutral, dried, transferred to a muffle furnace and calcined at 550° C. for 5 hours to obtain the product M-Mn-Beta molecular sieve.
[0117] The product mass was measured to be 1.5 g, the metal content was 0.9 wt%, and the specific surface area was 473 m 2 / g, and the crystallinity is 87%.
[0118] Embodiment 11
[0119] The performance of the M-Mn-Beta molecular sieve material in Example 1 in catalyzing the decarboxylation coupling reaction of cinnamic acid was studied.
[0120] 0.5 mmol cinnamic acid, 1.5 mmol sodium benzenesulfinate, 1.5 mmol% M-Mn-Beta (prepared in Example 1), 1.5 mmol potassium iodide and 4 ml dimethyl sulfoxide were added into a 15 ml three-necked flask with a magnetic stirring bar and reacted at 130° C. for 9 hours.
[0121] After the reaction is completed, the catalyst is separated by centrifugation, the reaction solution is detected and analyzed by SHIMADZU high performance liquid chromatography, and the product is separated by column chromatography.
[0122] The structure of the product was confirmed by NMR and HPLC to be (E)-(2-(phenylsulfonyl)vinyl)benzene, with a yield of 95.1%.
[0123] Product 1 H NMR spectrum Figure 5 As shown, 13 C NMR spectrum Figure 6 shown.
[0124] The NMR analysis of the product is: 1 H NMR (300MHz, CDCl3) δ8.02–7.88(m,2H),7.69(d,J=15.4Hz,1H),7.64–7.51(m,3H),7.50–7.34(m,5H),6.87(d,J=15.4Hz,1H). 13 C NMR (75MHz, CDCl3) δ142.5,140.7,133.4,132.4,131.3,129.4,129.1,128.6,127.7,127.3.
[0125] Test conditions:
[0126] SHIMADZU LC-VP high performance liquid chromatograph was used, and the mobile phase was acetonitrile and water gradient elution (V 乙腈 :V 水 =6:4), UV detector, detection wavelength is 274nm, flow rate is 1.0mL / min.
[0127] The AVANCE III 300M NMR instrument from Bruker, Germany, was used, with an operating frequency of 300 MHz ( 1 H); supershielded magnet, magnetic field strength 9.4T; equipped with a positive broadband liquid probe. Chemical shifts of protons are reported in ppm and are referenced to TMS or deuterated residues in NMR solvents (deuterated chloroform, δ7.26). Chemical shifts of carbon are reported in ppm and are referenced to the carbon resonance of the reference solvent (deuterated chloroform, δ77.16). Data represent coupling constants in Hertz (Hz), integrated.
[0128] Example 12
[0129] 0.5 mmol cinnamic acid, 0.5 mmol sodium benzenesulfinate, 1.5 mmol% M-Mn-Beta (prepared in Example 1), 1.5 mmol potassium iodide and 4 ml dimethyl sulfoxide were added into a 15 ml three-necked flask with a magnetic stirring bar and reacted at 130° C. for 9 hours.
[0130] The structure of the product was confirmed by NMR and HPLC to be (E)-(2-(phenylsulfonyl)vinyl)benzene, with a yield of 79.3%.
[0131] Example 13
[0132] 0.5 mmol cinnamic acid, 2.5 mmol sodium benzenesulfinate, 1.5 mmol% M-Mn-Beta, 1.5 mmol potassium iodide and 4 ml dimethyl sulfoxide were added into a 15 ml three-necked flask with a magnetic stirring bar and reacted at 130° C. for 9 hours.
[0133] The structure of the product was confirmed by NMR and HPLC to be (E)-(2-(phenylsulfonyl)vinyl)benzene, with a yield of 90.5%.
[0134] Embodiment 14
[0135] 0.5 mmol cinnamic acid, 1.5 mmol sodium benzenesulfinate, 0.1 mmol% M-Mn-Beta (prepared in Example 1), 1.5 mmol potassium iodide and 4 ml dimethyl sulfoxide were added into a 15 ml three-necked flask with a magnetic stirring bar and reacted at 130° C. for 9 hours.
[0136] The structure of the product was confirmed by NMR and HPLC to be (E)-(2-(phenylsulfonyl)vinyl)benzene, and the yield was only 6.3% because the use of too low an amount of the M-Mn-Beta catalyst would greatly reduce the reaction efficiency.
[0137] Embodiment 15
[0138] 0.5 mmol cinnamic acid, 1.5 mmol sodium benzenesulfinate, 5.0 mmol% M-Mn-Beta (prepared in Example 1), 1.5 mmol potassium iodide and 4 ml dimethyl sulfoxide were added into a 15 ml three-necked flask with a magnetic stirring bar and reacted at 130° C. for 9 hours.
[0139] The structure of the product was confirmed by NMR and HPLC to be (E)-(2-(phenylsulfonyl)vinyl)benzene, with a yield of 91.6%.
[0140] Example 16
[0141] 0.5 mmol cinnamic acid, 1.5 mmol sodium benzenesulfinate, 1.5 mmol% M-Mn-Beta (prepared in Example 1), 0.5 mmol potassium iodide and 1 ml dimethyl sulfoxide were added to a 15 ml three-necked flask with a magnetic stirring bar and reacted at 130° C. for 9 hours.
[0142] The structure of the product was confirmed by NMR and HPLC to be (E)-(2-(phenylsulfonyl)vinyl)benzene, with a yield of 8.5%, indicating that reducing the amount of the additive potassium iodide and the solvent dimethyl sulfoxide at the same time can significantly reduce the yield of the reaction, and further indicating that potassium iodide and dimethyl sulfoxide are crucial to the reaction.
[0143] Embodiment 17
[0144] 0.5 mmol cinnamic acid, 1.5 mmol sodium benzenesulfinate, 1.5 mmol% M-Mn-Beta (prepared in Example 1), 2.5 mmol potassium iodide and 10 ml dimethyl sulfoxide were added to a 15 ml three-necked flask with a magnetic stirring bar and reacted at 130° C. for 9 hours.
[0145] The structure of the product was confirmed by NMR and HPLC to be (E)-(2-(phenylsulfonyl)vinyl)benzene, with a yield of 87.2%.
[0146] Embodiment 18
[0147] 0.5 mmol cinnamic acid, 1.5 mmol sodium benzenesulfinate, 1.5 mmol% M-Mn-Beta (prepared in Example 1), 1.5 mmol sodium iodide and 4 ml N,N-dimethylformamide were added into a 15 ml three-necked flask with a magnetic stirring bar and reacted at 130° C. for 9 hours.
[0148] The structure of the product was confirmed by NMR and HPLC to be (E)-(2-(phenylsulfonyl)vinyl)benzene, with a yield of 70.3%.
[0149] Embodiment 19
[0150] 0.5 mmol cinnamic acid, 1.5 mmol sodium benzenesulfinate, 1.5 mmol% M-Mn-Beta (prepared in Example 1), 1.5 mmol ammonium iodide and 4 ml N,N-dimethylacetamide were added into a 15 ml three-necked flask with a magnetic stirring bar and reacted at 130° C. for 9 hours.
[0151] The structure of the product was confirmed by NMR and HPLC to be (E)-(2-(phenylsulfonyl)vinyl)benzene, with a yield of 61.5%.
[0152] Embodiment 20
[0153] 0.5 mmol cinnamic acid, 1.5 mmol sodium benzenesulfinate, 1.5 mmol% M-Mn-Beta (prepared in Example 1), 1.5 mmol iodine and 4 ml dichloroethane were added into a 15 ml three-necked flask with a magnetic stirring bar and reacted at 130° C. for 9 hours.
[0154] The structure of the product was confirmed by NMR and HPLC to be (E)-(2-(phenylsulfonyl)vinyl)benzene, and the yield was only 0.5%, indicating that when the additive was replaced with elemental iodine and the solvent was replaced with ethylene dichloride, the degree of the reaction was extremely low.
[0155] Embodiment 21
[0156] 0.5 mmol cinnamic acid, 1.5 mmol sodium benzenesulfinate, 1.5 mmol% M-Mn-Beta (prepared in Example 1), 1.5 mmol potassium carbonate and 4 ml N-methylpyrrolidone were added into a 15 ml three-necked flask with a magnetic stirring bar and reacted at 130° C. for 9 hours.
[0157] The structure of the product was confirmed by NMR and HPLC to be (E)-(2-(phenylsulfonyl)vinyl)benzene, and the yield was only 0.3%, indicating that potassium carbonate as an additive and N-methylpyrrolidone as a solvent were not suitable for the reaction system.
[0158] Embodiment 22
[0159] 0.5 mmol cinnamic acid, 1.5 mmol sodium benzenesulfinate, 1.5 mmol% M-Mn-Beta (prepared in Example 1), 1.5 mmol potassium chloride and 4 ml water were added into a 15 ml three-necked flask with a magnetic stirring bar and reacted at 130° C. for 9 hours.
[0160] The structure of the product was confirmed by NMR and HPLC to be (E)-(2-(phenylsulfonyl)vinyl)benzene with a yield of 16.5%, indicating that potassium chloride as an additive and water as a solvent are not the best choices for the reaction.
[0161] Embodiment 23
[0162] 0.5 mmol cinnamic acid, 1.5 mmol sodium benzenesulfinate, 1.5 mmol% M-Mn-Beta (prepared in Example 1), 1.5 mmol potassium bromide and 4 ml ethanol were added into a 15 ml three-necked flask with a magnetic stirring bar and reacted at 130° C. for 9 hours.
[0163] The structure of the product was confirmed by NMR and HPLC to be (E)-(2-(phenylsulfonyl)vinyl)benzene with a yield of 13.2%, indicating that potassium bromide as an additive and ethanol as a solvent are not the best choices for the reaction.
[0164] Embodiment 24
[0165] 0.5 mmol cinnamic acid, 1.5 mmol sodium benzenesulfinate, 1.5 mmol% M-Mn-Beta (prepared in Example 1), 1.5 mmol potassium iodide and 4 ml dimethyl sulfoxide were added into a 15 ml three-necked flask with a magnetic stirring bar and reacted at 50° C. for 1 hour.
[0166] The structure of the product was confirmed by NMR and HPLC to be (E)-(2-(phenylsulfonyl)vinyl)benzene with a yield of 2.8%, indicating that a simultaneous decrease in reaction temperature and reaction time would significantly reduce the efficiency of the reaction.
[0167] Embodiment 25
[0168] 0.5 mmol cinnamic acid, 1.5 mmol sodium benzenesulfinate, 1.5 mmol% M-Mn-Beta (prepared in Example 1), 1.5 mmol potassium iodide and 4 ml dimethyl sulfoxide were added to a 15 ml three-necked flask with a magnetic stirring bar and reacted at 70° C. for 9 hours.
[0169] The structure of the product was confirmed by NMR and HPLC to be (E)-(2-(phenylsulfonyl)vinyl)benzene, with a yield of 65.9%.
[0170] Embodiment 26
[0171] 0.5 mmol cinnamic acid, 1.5 mmol sodium benzenesulfinate, 1.5 mmol% M-Mn-Beta (prepared in Example 1), 1.5 mmol potassium iodide and 4 ml dimethyl sulfoxide were added to a 15 ml three-necked flask with a magnetic stirring bar and reacted at 100° C. for 24 hours.
[0172] The structure of the product was confirmed by NMR and HPLC to be (E)-(2-(phenylsulfonyl)vinyl)benzene, with a yield of 89.7%.
[0173] Embodiment 27
[0174] 0.5 mmol cinnamic acid, 1.5 mmol sodium benzenesulfinate, 1.5 mmol% M-Mn-Beta (prepared in Example 1), 1.5 mmol potassium iodide and 4 ml dimethyl sulfoxide were added into a 15 ml three-necked flask with a magnetic stirring bar and reacted at 150° C. for 20 hours.
[0175] The structure of the product was confirmed by NMR and HPLC to be (E)-(2-(phenylsulfonyl)vinyl)benzene, with a yield of 93.1%.
[0176] Embodiment 28
[0177] 0.5 mmol 2-methylcinnamic acid, 1.5 mmol sodium benzenesulfinate, 1.5 mmol% M-Mn-Beta (prepared in Example 1), 1.5 mmol potassium iodide and 4 ml dimethyl sulfoxide were added to a 15 ml three-necked flask with a magnetic stirring bar and reacted at 130° C. for 9 hours.
[0178] The structure of the product was confirmed by NMR and HPLC to be (E)-1-methyl-2-(2-(phenylsulfonyl)vinyl)benzene, with a yield of 78.2%.
[0179] The NMR analysis of the product is: 1 H NMR (300MHz, CDCl3) δ8.05–7.87(m,3H),7.66–7.51(m,3H),7.43(d,J=7.8Hz,1H),7.33–7.14(m,3H),6.79(d,J=15.3Hz,1H),2.45(s,3H). 13 CNMR(75MHz, CDCl3)δ140.7,140.1,138.2,133.4,131.4–130.9,129.4,128.1,127.7,126.9,126.5,19.8.
[0180] Embodiment 29
[0181] 0.5 mmol 3-methylcinnamic acid, 1.5 mmol sodium benzenesulfinate, 1.5 mmol% M-Mn-Beta (prepared in Example 1), 1.5 mmol potassium iodide and 4 ml dimethyl sulfoxide were added to a 15 ml three-necked flask with a magnetic stirring bar and reacted at 130° C. for 9 hours.
[0182] The structure of the product was confirmed by NMR and HPLC to be (E)-1-methyl-3-(2-(phenylsulfonyl)vinyl)benzene, with a yield of 82.3%.
[0183] The NMR analysis of the product is: 1 H NMR (300MHz, CDCl3) δ7.95(dt,J=3.6,2.5Hz,2H),7.71–7.46(m,4H),7.33–7.16(m,4H),6.85(d,J=15.4Hz,1H),2.34(s,3H). 13 C NMR (75MHz, CDCl3) δ142.7,140.8,138.9,133.4,132.2,129.5–128.9,127.7,127.0,125.9,21.3.
[0184] Embodiment 30
[0185] 0.5 mmol 2-ethoxycinnamic acid, 1.5 mmol sodium benzenesulfinate, 1.5 mmol% M-Mn-Beta (prepared in Example 1), 1.5 mmol potassium iodide and 4 ml dimethyl sulfoxide were added to a 15 ml three-necked flask with a magnetic stirring bar and reacted at 130° C. for 9 hours.
[0186] The structure of the product was confirmed by NMR and HPLC to be (E)-1-ethoxy-2-(2-(phenylsulfonyl)vinyl)benzene, with a yield of 75.1%.
[0187] The NMR analysis of the product is: 1 H NMR(300MHz, CDCl3)δ7.93(ddd,J=24.2,12.7,8.3Hz,1H),7.68–7.47(m,1H),7.43–7.27(m,1H),7 .09(d,J=15.5Hz,1H), 6.91(dd,J=15.5,8.0Hz,1H), 4.08(q,J=7.0Hz,1H), 1.43(t,J=7.0Hz,1H). 13 CNMR (75MHz, CDCl3) δ158.2,141.2,138.7,133.1,132.5,130.9,129.3,127.7,127.5,121.1,120.6,112.1,64.1,14.7.
[0188] Embodiment 31
[0189] 0.5 mmol 4-methoxycinnamic acid, 1.5 mmol sodium benzenesulfinate, 1.5 mmol% M-Mn-Beta (prepared in Example 1), 1.5 mmol potassium iodide and 4 ml dimethyl sulfoxide were added into a 15 ml three-necked flask with a magnetic stirring bar and reacted at 130° C. for 9 hours.
[0190] The structure of the product was confirmed by NMR and HPLC to be (E)-1-methoxy-4-(2-(phenylsulfonyl)vinyl)benzene, with a yield of 79.4%.
[0191] The NMR analysis of the product is: 1 H NMR (300MHz, CDCl3) δ7.98–7.90(m,2H),7.67–7.39(m,6H),6.95–6.84(m,2H),6.73(t,J=11.9Hz,1H),3.80(d,J=14.2Hz,3H). 13C NMR (75MHz, CDCl3) δ162.1,142.4,141.2,133.3,130.5,129.3,127.6,125.0,124.4,114.6,55.5.
[0192] Embodiment 32
[0193] 0.5 mmol 3-fluorocinnamic acid, 1.5 mmol sodium benzenesulfinate, 1.5 mmol% M-Mn-Beta (prepared in Example 1), 1.5 mmol potassium iodide and 4 ml dimethyl sulfoxide were added into a 15 ml three-necked flask with a magnetic stirring bar and reacted at 130° C. for 9 hours.
[0194] The structure of the product was confirmed by NMR and HPLC to be (E)-1-fluoro-3-(2-(phenylsulfonyl)vinyl)benzene, with a yield of 72.1%.
[0195] The NMR analysis of the product is: 1 H NMR (300MHz, CDCl3) δ8.03–7.88(m,2H),7.71–7.50(m,4H),7.44–7.33(m,1H),7.31–7.24(m,1H),7.22–7.06(m,2H),6.89(d,J=15.4Hz,1H). 13 CNMR (75MHz, CDCl3) δ164.6,161.3,141.0,141.0,140.3,134.6,134.5,133.6, 130.8,130.7,129.5,128.8,127.8,124.7,124.7,118.3,118.0,115.0,114.7.
[0196] Embodiment 33
[0197] 0.5 mmol 4-fluorocinnamic acid, 1.5 mmol sodium benzenesulfinate, 1.5 mmol% M-Mn-Beta (prepared in Example 1), 1.5 mmol potassium iodide and 4 ml dimethyl sulfoxide were added into a 15 ml three-necked flask with a magnetic stirring bar and reacted at 130° C. for 9 hours.
[0198] The structure of the product was confirmed by NMR and HPLC to be (E)-1-fluoro-4-(2-(phenylsulfonyl)vinyl)benzene, with a yield of 76.3%.
[0199] The NMR analysis of the product is: 1H NMR (300MHz, CDCl3) δ8.02–7.88(m,2H),7.69(d,J=15.4Hz,1H),7.64–7.51(m,3H),7.50–7.34(m,5H),6.87(d,J=15.4Hz,1H). 13 C NMR (75MHz, CDCl3) δ166.1,162.7,141.2,140.6,133.5,130.8,130.6,129.5,128.7,128.6,127.7,127.1,127.0,116.6,116.3.
[0200] Embodiment 34
[0201] 0.5 mmol 2,4-difluorocinnamic acid, 1.5 mmol sodium benzenesulfinate, 1.5 mmol% M-Mn-Beta (prepared in Example 1), 1.5 mmol potassium iodide and 4 ml dimethyl sulfoxide were added to a 15 ml three-necked flask with a magnetic stirring bar and reacted at 130° C. for 9 hours.
[0202] The structure of the product was confirmed by NMR and HPLC to be (E)-2,4-difluoro-1-(2-(phenylsulfonyl)vinyl)benzene, with a yield of 46.8%.
[0203] The NMR analysis of the product is: 1 H NMR (300MHz, CDCl3) δ8.00–7.89(m,2H),7.75–7.40(m,5H),7.00–6.81(m,3H). 13 C NMR (75MHz, CDCl3) δ140.4,134.5,133.6,131.6,130.0–129.4,127.8,112.5,105.4,105.0,104.7.
[0204] Embodiment 35
[0205] 0.5 mmol 2-chlorocinnamic acid, 1.5 mmol sodium benzenesulfinate, 1.5 mmol% M-Mn-Beta (prepared in Example 1), 1.5 mmol potassium iodide and 4 ml dimethyl sulfoxide were added into a 15 ml three-necked flask with a magnetic stirring bar and reacted at 130° C. for 9 hours.
[0206] The structure of the product was confirmed by NMR and HPLC to be (E)-1-chloro-2-(2-(phenylsulfonyl)vinyl)benzene, with a yield of 70.2%.
[0207] The NMR analysis of the product is: 1H NMR (300MHz, CDCl3) δ7.98–7.92(m,2H),7.76(d,J=15.6Hz,1H),7.66–7.51(m,3H),7.49–7.34(m,2H),7.20–6.98(m,3H). 13 C NMR (75MHz, CDCl3) δ163.3,159.9,140.5,135.6,135.6,133.6,132.9,132.8, 130.4,130.4,130.3,130.2,129.4,127.8,124.8,124.7,120.7,120.5,116.3.
[0208] Embodiment 36
[0209] 0.5 mmol 3-chlorocinnamic acid, 1.5 mmol sodium benzenesulfinate, 1.5 mmol% M-Mn-Beta (prepared in Example 1), 1.5 mmol potassium iodide and 4 ml dimethyl sulfoxide were added into a 15 ml three-necked flask with a magnetic stirring bar and reacted at 130° C. for 9 hours.
[0210] The structure of the product was confirmed by NMR and HPLC to be (E)-1-chloro-3-(2-(phenylsulfonyl)vinyl)benzene, with a yield of 66.7%.
[0211] The NMR analysis of the product is: 1 H NMR (300MHz, CDCl3) δ7.99–7.88(m,2H),7.69–7.51(m,4H),7.46(d,J=1.8Hz,1H),7.41–7.24(m,3H),6.88(d,J=15.4Hz,1H). 13 C NMR (75MHz, CDCl3) δ140.8,140.4,135.2,134.2,133.7,131.1,130.4,129.5,129.0,128.3,127.8,126.9.
[0212] Embodiment 37
[0213] 0.5 mmol 4-chlorocinnamic acid, 1.5 mmol sodium benzenesulfinate, 1.5 mmol% M-Mn-Beta (prepared in Example 1), 1.5 mmol potassium iodide and 4 ml dimethyl sulfoxide were added into a 15 ml three-necked flask with a magnetic stirring bar and reacted at 130° C. for 9 hours.
[0214] The structure of the product was confirmed by NMR and HPLC to be (E)-1-chloro-4-(2-(phenylsulfonyl)vinyl)benzene, with a yield of 72.3%.
[0215] The NMR analysis of the product is: 1 H NMR (300MHz, CDCl3) δ7.99–7.89(m,2H),7.67–7.50(m,4H),7.45–7.31(m,4H),6.85(d,J=15.4Hz,1H). 13 C NMR (75MHz, CDCl3) δ141.0,140.5,137.3,133.6,130.9,129.8,129.5,128.0,127.7.
[0216] Embodiment 38
[0217] 0.5 mmol 3-bromocinnamic acid, 1.5 mmol sodium benzenesulfinate, 1.5 mmol% M-Mn-Beta (prepared in Example 1), 1.5 mmol potassium iodide and 4 ml dimethyl sulfoxide were added into a 15 ml three-necked flask with a magnetic stirring bar and reacted at 130° C. for 9 hours.
[0218] The structure of the product was confirmed by NMR and HPLC to be (E)-1-bromo-3-(2-(phenylsulfonyl)vinyl)benzene, with a yield of 62.6%.
[0219] The NMR analysis of the product is: 1 H NMR (300MHz, CDCl3) δ7.97(dt,J=3.6,2.4Hz,2H),7.71–7.50(m,6H),7.41(t,J=7.9Hz,1H),7.29(dd,J=8.8,6.9Hz,1H),6.90(d,J=15.4Hz,1H). 13 C NMR (75MHz, CDCl3) δ140.7,140.3,134.4,134.0,133.7,131.1,130.6,129.5,128.9,127.8,127.3,123.2.
[0220] Embodiment 39
[0221] 0.5 mmol cinnamic acid, 1.5 mmol sodium 4-methylbenzenesulfinate, 1.5 mmol% M-Mn-Beta (prepared in Example 1), 1.5 mmol potassium iodide and 4 ml dimethyl sulfoxide were added into a 15 ml three-necked flask with a magnetic stirring bar and reacted at 130° C. for 9 hours.
[0222] The structure of the product was confirmed by NMR and HPLC to be (E)-1-methyl-4-(styrenesulfonyl)benzene, with a yield of 91.5%.
[0223] The NMR analysis of the product is: 1 H NMR (300MHz, CDCl3) δ7.86–7.79(m,2H),7.64(t,J=10.3Hz,1H),7.50–7.43(m,2H),7.42–7.29(m,5H),6.84(t,J=9.8Hz,1H),2.44–2.39(m,3H). 13 C NMR (75MHz, CDCl3) δ144.4,141.9,137.7,132.4,131.1,130.0,129.1,128.5,127.7,21.6.
[0224] Embodiment 40
[0225] 0.5 mmol cinnamic acid, 1.5 mmol sodium 4-fluorobenzenesulfinate, 1.5 mmol% M-Mn-Beta (prepared in Example 1), 1.5 mmol potassium iodide and 4 ml dimethyl sulfoxide were added into a 15 ml three-necked flask with a magnetic stirring bar and reacted at 130° C. for 9 hours.
[0226] The structure of the product was confirmed by NMR and HPLC to be (E)-1-fluoro-4-(styrenesulfonyl)benzene, with a yield of 88.2%.
[0227] The NMR analysis of the product is: 1 H NMR (300MHz, CDCl3) δ8.02–7.89(m,2H),7.68(d,J=15.4Hz,1H),7.53–7.34(m,5H),7.28–7.16(m,2H),6.90–6.78(m,1H). 13 C NMR (75MHz, CDCl3) δ167.4,164.0,142.7,136.8,132.3,131.4,130.6,129.2,128.7,127.1,116.9,116.6.
[0228] Embodiment 41
[0229] 0.5 mmol cinnamic acid, 1.5 mmol sodium 4-chlorobenzenesulfinate, 1.5 mmol% M-Mn-Beta (prepared in Example 1), 1.5 mmol potassium iodide and 4 ml dimethyl sulfoxide were added into a 15 ml three-necked flask with a magnetic stirring bar and reacted at 130° C. for 9 hours.
[0230] The structure of the product was confirmed by NMR and HPLC to be (E)-1-chloro-4-(styrenesulfonyl)benzene, with a yield of 82.1%.
[0231] The NMR analysis of the product is: 1 H NMR (300MHz, CDCl3) δ7.93–7.83(m,2H),7.68(d,J=15.4Hz,1H),7.55–7.44(m,4H),7.43–7.33(m,3H),6.85(d,J=15.4Hz,1H). 13 C NMR (75MHz, CDCl3) δ143.1,140.1,139.3,132.2,131.5,129.7,129.2,128.7,126.8.
[0232] Embodiment 42
[0233] M-Mn-Beta cycle test:
[0234] 0.5 mmol cinnamic acid, 1.5 mmol sodium benzenesulfinate, 1.5 mmol% M-Mn-Beta (prepared in Example 1), 1.5 mmol potassium iodide and 4 ml dimethyl sulfoxide were added into a 15 ml three-necked flask with a magnetic stirring bar and reacted at 130° C. for 9 hours.
[0235] After the reaction, the catalyst was centrifuged, washed several times with deionized water and anhydrous ethanol, and then placed in a drying oven at 100°C for 12 hours. The dried catalyst was recycled six times under the same catalytic conditions. The catalytic effect was as follows: Figure 7 As shown, the results show that the catalytic activity remains basically unchanged after six cycles.
[0236] Comparative Example 3
[0237] 0.5 mmol cinnamic acid, 1.5 mmol sodium benzenesulfinate, 1.5 mmol% manganese chloride tetrahydrate, 1.5 mmol potassium iodide and 4 ml dimethyl sulfoxide were added into a 15 ml three-necked flask with a magnetic stirring bar and reacted at 130° C. for 9 hours.
[0238] The structure of the product was confirmed by NMR and HPLC to be (E)-(2-(phenylsulfonyl)vinyl)benzene, with a yield of 23.5%.
[0239] Comparative Example 4
[0240] 0.5 mmol cinnamic acid, 1.5 mmol sodium benzenesulfinate, 1.5 mmol% nano manganese chloride, 1.5 mmol potassium iodide and 4 ml dimethyl sulfoxide were added into a 15 ml three-necked flask with a magnetic stirring bar and reacted at 130° C. for 9 hours.
[0241] The structure of the product was confirmed by NMR and HPLC to be (E)-(2-(phenylsulfonyl)vinyl)benzene, with a yield of 15.7%.
[0242] Comparative Example 5
[0243] 0.5 mmol cinnamic acid, 1.5 mmol sodium benzenesulfinate, 1.5 mmol% Beta molecular sieves, 1.5 mmol potassium iodide and 4 ml dimethyl sulfoxide were added into a 15 ml three-necked flask with a magnetic stirring bar and reacted at 130° C. for 9 hours.
[0244] The structure of the product was confirmed by NMR and HPLC to be (E)-(2-(phenylsulfonyl)vinyl)benzene, with a yield of 0.2%.
[0245] Comparative Example 6
[0246] 0.5 mmol cinnamic acid, 1.5 mmol sodium benzenesulfinate, 1.5 mmol% M-Mn-Beta (prepared by ion exchange method), 1.5 mmol potassium iodide and 4 ml dimethyl sulfoxide were added into a 15 ml three-necked flask with a magnetic stirring bar and reacted at 130° C. for 9 hours.
[0247] The structure of the product was confirmed by NMR and HPLC to be (E)-(2-(phenylsulfonyl)vinyl)benzene, with a yield of 51.6%.
[0248] Comparative Example 7
[0249] 0.5 mmol cinnamic acid, 1.5 mmol sodium benzenesulfinate, 1.5 mmol% M-Mn-Beta (prepared by equal volume impregnation method), 1.5 mmol potassium iodide and 4 ml dimethyl sulfoxide were added to a 15 ml three-necked flask with a magnetic stirring bar and reacted at 130°C for 9 hours.
[0250] The structure of the product was confirmed by NMR and HPLC to be (E)-(2-(phenylsulfonyl)vinyl)benzene, with a yield of 63.8%.
[0251] The invention discloses a method for synthesizing an acidic Beta zeolite molecular sieve catalyst containing a mesoporous structure by in-situ doping hydrothermal method of metal manganese and its application in catalyzing the decarboxylation coupling reaction of cinnamic acid to generate a vinyl sulfone compound, and relates to the field of heterogeneous catalysts for constructing vinyl sulfone compounds by decarboxylation coupling reaction. The in-situ doping hydrothermal preparation method comprises: using silicic acid, sodium metaaluminate and manganese salt as raw materials, crystallizing at a constant temperature of 140°C for 14 days in the presence of a quaternary ammonium salt template, and obtaining an M-Mn-Beta molecular sieve catalyst with a specific surface area of 435 to 693 m 2 / g, the silicon-aluminum ratio is 20:1-60:1, and the crystallinity is 85-100%. The prepared catalyst has the advantages of economy, high efficiency, green environmental protection, etc., and can improve the disadvantages of homogeneous catalysts that are difficult to recover and recycle.
[0252] The preparation method of the invention is easy to operate and has good reproducibility. The acidic M-Mn-Beta molecular sieve containing a mesoporous structure is used to catalyze the decarboxylation coupling reaction of cinnamic acid and sodium benzenesulfinate, and the yield of the obtained (E)-(2-(phenylsulfonyl)vinyl)benzene can be as high as 95%. After the catalyst is recycled for multiple times, it still maintains a high catalytic activity and there is no metal loss. Therefore, it can be applied to the fields of modern organic catalytic synthesis of organic vinyl sulfone compounds, and has a certain industrial application prospect.
[0253] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.
Claims
1. An application of a manganese-doped acidic Beta zeolite molecular sieve containing a mesoporous structure, characterized in that: The acidic Beta zeolite molecular sieve is used to catalyze the decarboxylation sulfonylation reaction of cinnamic acid and sodium benzenesulfinate to prepare a vinyl sulfone compound, wherein the preparation method comprises mixing cinnamic acid, sodium benzenesulfinate, an acidic Beta molecular sieve catalyst M-Mn-Beta, an additive and a solvent, and reacting at 50 to 150° C. for 1 to 24 hours to obtain a vinyl sulfone silicon compound; The cinnamic acid is cinnamic acid and its derivatives, at least one of 2-methylcinnamic acid, 3-methylcinnamic acid, 2-ethoxycinnamic acid, 4-methoxycinnamic acid, 3-fluorocinnamic acid, 4-fluorocinnamic acid, 2,4-difluorocinnamic acid, 2-chlorocinnamic acid, 3-chlorocinnamic acid, 4-chlorocinnamic acid, and 3-bromocinnamic acid; the sodium benzenesulfinate is sodium benzenesulfinate and its derivatives, at least one of 4-methylbenzenesulfinate, 4-fluorobenzenesulfinate, and 4-chlorobenzenesulfinate; the molar ratio of cinnamic acid to sodium benzenesulfinate is 1:1 to 1:5; the amount of the acidic Beta molecular sieve catalyst M-Mn-Beta added is 0.1 to 5 mol% of the amount of cinnamic acid; The additive is one of KI, NaI, NH4I, I2, K2CO3, KCl, and KBr, and each 0.1 mmol of cinnamic acid corresponds to 0.1 to 0.5 mmol of the additive; the solvent is one or more of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, dichloroethane, N-methylpyrrolidone, water, and ethanol, and each 0.1 mmol of cinnamic acid corresponds to 0.2 to 2 ml of the solvent; The vinyl sulfone silicon compound is used in the field of catalytic organic synthesis chemistry, medicinal chemistry or material science; The structure of the molecular sieve is Mn-nSi-Al-Beta, wherein n represents the molar ratio of Si / Al, and n=20 to 60; The acidic Beta zeolite molecular sieve has a characteristic X-ray powder diffraction pattern as shown below: The X-ray powder diffraction pattern is based on a relative intensity scale, wherein the strongest line in the X-ray powder diffraction pattern is assigned a value of 100, and the corresponding relative intensities are: w represents weak, i.e. ≤20; m represents medium, i.e. >20 to ≤40; s represents strong, i.e. >40 to ≤60; and vs represents very strong, i.e. >60.
2. The use according to claim 1, characterized in that: The specific surface area of the acidic Beta zeolite molecular sieve is 435 to 693 m 2 / g, the silicon-aluminum ratio is 20:1-60:1, and the crystallinity is 85-100%.
3. The use according to claim 1 or 2, characterized in that: The preparation method of the acidic Beta zeolite molecular sieve comprises: Mix silicic acid, manganese salt and deionized water evenly, add concentrated hydrochloric acid dropwise to adjust the pH to 1.0, then add quaternary ammonium salt and sodium aluminate, stir evenly and adjust the pH of the solution to 12.5 with sodium hydroxide; The mixed solution is transferred to a hydrothermal autoclave with a polytetrafluoroethylene liner and crystallized at a constant temperature for a period of time; The product was washed with deionized water and anhydrous ethanol, dried, and calcined at 550° C. for 5 hours to obtain a manganese-doped acidic Beta molecular sieve catalyst M-Mn-Beta containing a mesoporous structure.
4. The use according to claim 3, characterized in that: The molar ratio of the silicic acid to the sodium aluminate is 20:1 to 60:
1.
5. The use according to claim 3, characterized in that: The quaternary ammonium salt is one or more of tetraethylammonium bromide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, and hexadecyltrimethylammonium bromide, and 1.2 to 3 g of the quaternary ammonium salt corresponds to every 1 g of silicic acid; the manganese salt is one or more of manganese nitrate, manganese acetate, manganese sulfate, and manganese chloride, and 0.03 to 0.1 g of the manganese salt corresponds to every 1 g of silicic acid.
6. The use according to claim 3, characterized in that: The constant temperature crystallization is performed for a period of time at a certain temperature, wherein the crystallization temperature is 100-200° C. and the crystallization time is 5-15 days.
Citation Information
Patent Citations
Method for preparing BEA type molecular sieves and BEA type molecular sieve
CN109911913A